Calorific Value of Palm Kernel Shell Charcoal (PKSC) Briquette as Solid Fuel - Hendri Nurdin; Waskito Waskito; Fadhilah Fadhilah; Toto Sugiarto; Andre Kurniawan; Yolli Fernanda; Rudy Anarta; Fathi Aulia DZ (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The need and utilization of energy in society exceed available production. This condition requires acceleration and efforts to find solutions through the diversification of palm shell biomass into solid fuel briquettes. Palm shells have the potential as biomass and renewable energy sources that are selected based on strategic, technical, and environmental considerations. Its utilization so far has only been burned directly which causes air pollution or used as road paving in oil palm plantations. The environmental impact is the accumulation of solid waste, and global warming in the Crude Palm Oil processing industry. The research objective was to obtain the calorific value of palm kernel shell briquettes with carbonization process. The experimental research method carried out by innovating palm kernel shell briquette raw materials at various percentage variances (90%: 10%, 85%: 15%, 80%: 20%, 75%: 25%) using tapioca adhesive. The technical parameters of briquettes making are molding pressure of 10 MPa, particle grains of 60 mesh, carbonization temperature of 400oC; 450oC; 500oC with a holding time of 1 hour. From this study, the calorific value of palm kernel shell charcoal (PKSC) briquettes at a concentration of 85%;15% at a temperature of 400oC was 25.86 MJ/kg with tapioca adhesives as the highest calorific value parameters. The technology used to make palm kernel shell charcoal briquettes is a potential development that can be recommended as a precursor to solid fuels. The impact of developing PKSC biomass energy briquettes is an innovation in utilizing waste to create solid fuels. The implications of this research can be applied by home industries or households. This research is a contribution to solutions in overcoming energy needs and deficiencies as a form of sustainable energy..